Liberación del ion flúor de un cemento de ionómero vítreo modificado con extracto etanólico de propóleo - Lezcano, Melisa Raquel (2021)
Objective. The objective of this study was to quantify the release of flavonoids and fluoride in test tubes of conventional type II vitreous ionomer modified with propolis extract. Methods. Sixty units of analysis were used. The 2% propolis ethanolic extract was incorporated into a type II glass ionomer. To determine the release of flavonoids, the laboratory analyzed the concentration of quercetin per ml of solution, either distilled water or physiological solution, during a period of 5 days. Results. There was an initial release of 0.40 mg/ml of fluorine in physiological solution and 0.35 mg / ml of fluorine in distilled water, and a final release of 0 mg/ml of flavonoids and fluorine in physiological solution and of 0,18 mg/ml of fluorine in distilled water solution. Conclusions. The release of fluoride and flavonoids occurs in greater concentration in the first hours, decreasing as the hours go by.